2011
DOI: 10.1182/blood-2011-02-335216
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathy-associated T-cell lymphoma: clinical and histological findings from the International Peripheral T-Cell Lymphoma Project

Abstract: Few large, international series of enteropathy-associated T-cell lymphoma (EATL) have been reported. We studied a cohort of 62 patients with EATL among 1153 patients with peripheral T-cell or natural killer (NK)-cell lymphoma from 22 centers worldwide. The diagnosis was made by a consensus panel of 4 expert hematopathologists using World Health Organization (WHO) criteria. Clinical correlations and survival analyses were performed. EATL comprised 5.4% of all lymphomas in the study and was most common in Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
319
3
20

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(352 citation statements)
references
References 33 publications
(49 reference statements)
10
319
3
20
Order By: Relevance
“…These results are consistent with the immunophenotype of Type II EATL as previously described. [1][2][3][4][5][6] In the present study, a high proportion of cases expressed γδ-TCR (10/20, 50%), and six cases were negative for both αβ and γδ-TCR, a finding that differs from the description in the WHO classification, which states that EATL Type II cases express αβ-TCR. Tan et al 7 reported predominant expression of αβ-TCR over γδ-TCR, and Chan et al 8 reported that 78% of Type II EATL cases expressed γδ-TCR.…”
Section: Discussioncontrasting
confidence: 89%
“…These results are consistent with the immunophenotype of Type II EATL as previously described. [1][2][3][4][5][6] In the present study, a high proportion of cases expressed γδ-TCR (10/20, 50%), and six cases were negative for both αβ and γδ-TCR, a finding that differs from the description in the WHO classification, which states that EATL Type II cases express αβ-TCR. Tan et al 7 reported predominant expression of αβ-TCR over γδ-TCR, and Chan et al 8 reported that 78% of Type II EATL cases expressed γδ-TCR.…”
Section: Discussioncontrasting
confidence: 89%
“…Retrospective studies in Western populations have shown that it represents 10%-16% of all primary lymphomas of the GI tract [1,2]. In another recent international study, it accounted for 5.4% of all lymphomas [3]. EATL in its classical form is predominantly found in Western countries, especially in northern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The immunophenotype is also distinct from classical EATL, being CD3 1 , CD4 -, CD8 1 , and D56 1 . It is less common in Western countries, accounting for 10%-20% of the cases in published series of EATL [1][2][3][4][5]. It is currently undefined if type II EATL is a histologic variant of classical EATL or represents a separate lymphoma entity.…”
Section: Introductionmentioning
confidence: 99%
“…In some patients, EATL presents in individuals with established CD who have previously responded well to a GFD but are now symptomatic due to developing RCD and/or classic EATL [9]. Other patients present acutely with a small bowel obstruction or perforation, and this can be seen in individuals with prior undiagnosed CD or without a history of CD (EATL Type II).…”
Section: Discussionmentioning
confidence: 99%